Becoming a personal style blogger: Changing configurations and spatialities of aesthetic labour in the fashion industry. (January 2019) - Brydges, Taylor; Sjöholm, Jenny
The increasing pervasiveness of social media and digital technology has had a particular impact on the geographies and nature of work in the fashion industry. A new segment of entrepreneurs – fashion bloggers – are utilizing these digital technologies, such as blogs and social media, to transform their personal lives and style into online businesses. This article draws on an in-depth case study analysis of an American personal style fashion blog; tracing its nine-year evolution from an 'outfit-of-the-day' personal style blog, to one that encompasses her entire personal life, including diets, fitness, home décor and pregnancy. By focusing on one blog, we provide an in-depth exploration from its roots as a hobby for personal expression to a means of full-time employment in the fashion industry. Through this examination, emphasis is given to the process of becoming a blogger and the intensification of the ways in which the self is presented and commodified over time. We argue that personal style fashion bloggers provide an illustrative case study, not only for expanding our understanding of aesthetic labour in the digital age, but also highlighting the spaces and temporalities of work that these new formations and engagements of work give rise to. These processes highlight the changing configurations and spatialities of aesthetic labour online.